Balancing Resettlement, Protection and Rapport on the Frontline: Delivering the Resettlement Assistance Program during COVID-19 - Abbas, Saba (Refuge: Canada’s Journal on Refugees, 2022)
Drawing on my experience as a general counsellor in the Resettlement Assistance Program (RAP), I explore the impact COVID-19 has had on the initial resettlement services provided for government-assisted refugees (GARs) and on frontline workers in the field. Balancing the requirement to enforce protection measures and the need to establish rapport was one of the major challenges the pandemic posed to GAR support practices. To unpack the particularities of this challenge, I give the example of two resettlement services GARs receive upon arrival: namely, resettlement orientations and children’s education. I argue that using an intersectional lens demonstrates the pandemic’s unequal effects and how they exacerbate the vulnerabilities of GARs embarking on their resettlement journey. I hold that developing COVID-19 responses informed by intersectionality opens a space for services and policies that mitigate these effects.